Does Age Matter? A Behavioral Contingency Approach to University Governance - Najeh Wassim Abdessalam; Rania Rejjaoui; Aya Mahir; Houda Benarbi (goodwood publishing, 2026)
Purpose: The objective of this study is to examine how age, acting as a metacognitive contingency factor, influences decision-making processes in university governance and affects the perceived organizational performance of Moroccan universities. The research aims to shift the focus from traditional financial metrics to behavioral factors, such as cognitive and metacognitive processes, to understand how they guide the actions of decision-makers Research Methodology: This study was conducted in Moroccan universities using a quantitative research design and a positivist epistemological stance. Data were collected via a structured survey questionnaire administered through Microsoft Forms over a five-month period, resulting in 163 valid responses from academic and administrative actors. The sample size was determined using Slovin’s formula (1960). Data analysis was performed using Jamovi software. Results: The empirical findings indicate that chronological age has no statistically significant direct impact on performance indicators, such as working conditions, communication quality, or satisfaction. In contrast, professional experience showed a significant positive relationship with communication quality but a negative correlation with overall satisfaction. Furthermore, the perceived openness to change of young administrators was found to be positively associated with working conditions Conclusions: The study concludes that biological age is not a direct determinant of organizational performance outcomes within the Moroccan university context. Instead, factors like professional experience and specific perceptions of administrative attitudes (such as openness to change) are more influential drivers of performance perceptions. Age may function as a moderating variable that influences cognitive processes indirectly or in a context-dependent manner Limitations: primary limitation of this study is the sample size of 163 responses from a total population of 38,556, which results in an estimated margin of error of approximately 7.8%, requiring the results to be interpreted with caution. While the literature recognizes that multiple behavioral determinants such as academic background may shape leadership practices, this study deliberately concentrates on age as the principal behavioral contingency variable. Contributions: This study advances Management Science and University Governance by applying Behavioral Contingency Theory to higher education. It underscores that leaders’ cognitive profiles and experiences are as critical as material resources in shaping governance, while illuminating the psychological drivers of decision-making in the Moroccan university context.